2014
DOI: 10.1021/ma501541g
|View full text |Cite
|
Sign up to set email alerts
|

ATRP of POSS Monomers Revisited: Toward High-Molecular Weight Methacrylate–POSS (Co)Polymers

Abstract: For the first time, ATRP was successfully employed for homopolymerization of a commercial methacrylate-functionalized polyhedral oligomeric silsesquioxane (POSS) monomer, iBuPOSSMA, to high molecular weights. It was found that iBuPOSSMA has a low ceiling temperature (T c); therefore, low temperatures and/or high initial monomer concentrations need to be used in order to avoid low degrees of polymerization that had been observed previously. The values of T c, as well as of the polymerization enthalpy ΔH p and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 53 publications
7
56
1
Order By: Relevance
“…The highest conversion (95%) was reached with Me 6 TREN (entry 4). This value corresponds well to the limiting conversion of ≈97% that can be estimated from the thermodynamic parameters we determined in our previous study . The M n values obtained by size‐exclusion chromatography (SEC) with polystyrene standards are known to be considerably underestimated; however, realistic values [ M n (est.)]…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…The highest conversion (95%) was reached with Me 6 TREN (entry 4). This value corresponds well to the limiting conversion of ≈97% that can be estimated from the thermodynamic parameters we determined in our previous study . The M n values obtained by size‐exclusion chromatography (SEC) with polystyrene standards are known to be considerably underestimated; however, realistic values [ M n (est.)]…”
Section: Resultssupporting
confidence: 85%
“…Various factors might be responsible for the decreased polymerization rates observed when high‐MW poly( i BuPOSSMA) are aimed. As has been shown previously, depropagation becomes increasingly prominent as the monomer conversion increases, diminishing gradually the efficient rate constant of propagation ( k p eff ) . In addition, the polymerization mixtures tend to be rather diluted (in molar terms) due to the high MW and limited solubility of the solid i BuPOSSMA monomer.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…In the cubic POSS, Si atoms occupy the corners of a cube and oxygen atoms located at the edges of core (2,3), but peripheral organic groups in the shell give them several advantages over conventional inorganic particles with a wide variety of potential substituent groups attached (4). The choice of substituent groups not only provides POSS selective solubility in organic or aqueous solvents, but also the ability dispersed in many polymers and the specific chemical reactivity of different substituent groups that can be directly incorporated the POSS into polymer backbones or side groups or networks by covalent bonding (5)(6)(7)(8)(9)(10)(11). Therefore, the outer shell of POSS effectively controls the interaction between the POSS units and the surrounding matrix (12).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the outer shell of POSS effectively controls the interaction between the POSS units and the surrounding matrix (12). What is more, the shell substituents could offer immense opportunities for synthesis of organic-inorganic hybrid copolymers (5)(6)(7)(8)(9)(10)(11). It has been reported that the introduction of POSS into polymers can distinctly enhance the native polymer properties in glass transition temperature (13)(14), decomposition temperature (15), surface hardness, mechanical properties, flammability resistance and oxidation resistance attributed to the inorganic octahedral cage structure of POSS (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%